Digitization of Exhibition Spaces: Educational and Cultural Dissemination Tool in the Connected Society - Santín Álvarez, Eva; Blanco Marcos, Jessica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The digitization of exhibition spaces transforms the perception and access to cultural and artistic content, expanding access to exhibitions and redefining the interaction between users, technology and culture. The DEXED project proposes a standard methodology for digitizing exhibitions, integrating immersive technologies (360º tours, augmented reality, interactive repositories). DEXED aims to enrich both virtual and in-person experiences, establishing a replicable model. Social media amplifies the visibility of cultural content and encourages active public participation. DEXED connects technology, art, literature, and education in a dynamic digital ecosystem, transforming exhibitions into interactive and participatory experiences.